Konsep Keberanian dan Pantang Menyerah pada Tokoh Sugimoto dan Asirpa dalam Anime Golden Kamuy - Muhammad Mahir Rahman; Antonius R. Pujo Purnomo (KIRYOKU, 2023)
This study mainly discusses about bravery and unyielding from character Asirpa and Sugimoto in anime “The Golden Kamuy”(2018).  Bravery is an element needed to survive in life and fighting the enemy. Bravery and unyielding are represented through various thrilling and heroic actions. This study aims to: 1) explain the background of the Ainu in the historical, social and cultural context; 2) identify the Bushido code of Asirpa and Sugimoto; and 3) analyzing the aspects of bravery and unyielding in each scene. The research method used qualitative with the subject matter of this research viewed from anthropological and sociological aspects. The data used from the Japanese animation “Golden Kamuy”. This anime shows the life of the Ainu people who are the focus of this research who lives in the northern part of Japan and Russia and depends on hunting and fishery. In the anime at least some elements of bravery and unyielding which are: 1) Sugimoto tried to kill Russian soldiers alone when his friends were dead; 2) when Sugimoto tries to catch a big bear with Asirpa at night; 3) Sugimoto was interrogated by Lieutenant Tsurumi regarding the whereabouts of prisoners carrying gold nuggets belonging to the Ainu tribe; and 4) Sugimoto tried to save a prisoner who had died at sea. This incident is an example of an attitude of bravery and unyielding which will be discussed in the following research using the interpretation of Bushido code.